Extra-vascular findings in patients undergoing magnetic resonance angiography of the abdomen, pelvis and lower extremities: A retrospective study of 352 patients. (February 2018) - Sohns, Jan M; Menke, Jan; Bergau, Leonard; Weiss, Bernhard G; Schmuck, Sebastian; Weiberg, Desiree; Staab, Wieland; Derlin, Thorsten; Dorenkamp, Marc; Sohns, Christian
Background: The aim of this study was to assess the prevalence and clinical significance of extra-vascular findings in patients undergoing magnetic resonance angiography of the abdomen, pelvis and lower extremities. Materials and methods: Three hundred fifty-two patients underwent abdominal, pelvic and lower extremity 1.5 T magnetic resonance angiography. Clinically relevant vascular and extra-vascular findings were identified. Relevant vascular findings were classified as stenosis, occlusion, aneurysm, sclerosis, dissection or vasculitis. Relevant extra-vascular findings were categorized as 'safe' (Group A), intermediate – requiring additional investigation – (Group B) and malignant/endangering – requiring change of therapy (Group C). Results: A total of 2152 clinically relevant vascular findings was identified (6.1/patient). The most frequent vascular finding was femoral artery stenosis (10.6%). Four hundred fifty-one extra-vascular findings were observed (1.3/patient) and classified into Group A (78%), Group B (19.5%) and Group C findings (2.4%). The most frequent malignant findings were lung cancer, lymphoma, osteosarcoma, hepatocellular carcinoma and renal cell carcinoma (7/352 patients). Conclusions: Extravascular findings are frequently encountered in magnetic resonance angiography performed for vascular indications. Clinically relevant findings are seen in a substantial part of patients and should prompt further diagnostic work-up.